The role of digital platforms in the transfer of knowledge and qualificationism: A study of digital sociology - Dwiki Faiz Sarvianto (SIMULACRA: JURNAL SOSIOLOGI, 2020)
Indonesia has entered the digital era. Many sectors have been affected by the development of existing digital devices and platforms, including the higher education sector. Sociologically, this influence must be anticipated because it will influence the transfer of knowledge and the phenomenon of qualification. If the transfer of knowledge is ineffective, the quality of the individual produced by the higher education level may be incompetent. This study aimed to dissect the role and attention on the transfer of knowledge that occurs, along with its impact during the digital era. This study used a qualitative approach with descriptive methods through literature study techniques to synthesize existing empirical facts. The primary empirical data analyzed was the results of research on the transfer of specific knowledge and the phenomenon of qualificationism. The researcher found that digitalization influenced online learning and publication that were inter-related, despite differences in access, skills and benefits for individuals. On the other hand, the quality of higher education faced challenges because there was tacit knowledge that must be fulfilled and the phenomenon of qualification as the impact of higher education growth.